Substantial potential effects on single-atom catalysts for the oxygen evolution reaction simulated via a fixed-potential method - Gao, Guoping; Wang, Lin-Wang (Journal of catalysis, 2020)
[Display omitted] •A fixed potential method is used to simulate potential effects in electrochemical reactions.•Adjustes the total system charge to satisfy the applied electrode potential.•Yield different rate-limiting steps and overpotential Potential not only governs the direction of electrochemical reactions, but also shapes the electronic properties of single-atom catalysts dramatically. However, it is a challenge to simulate the effects of potential theoretically. Normally, DFT calculations are performed at a constant number of electrons, not a constant voltage. In this work, we apply a new fixed-potential method (grand canonical method) in the DFT simulation to mimic the electrochemical processes, in which the total number of the electron in the system was floated to match the ‘‘applied voltage,’, or the electrode Fermi energy at the atomic level. Here, the single-atom catalysts on two-dimension substrates for the oxygen evolution reaction process are used as examples to test the fixed-potential method. This fixed-potential method changes the rate-determining step and yields an overpotential difference of as much as 0.48 V in comparison with the conventional charge-neutral method. The quantitative error in the overpotential is not as important as the qualitative error in rate-determining steps. These errors can be avoided via the fixed-charge method with the proper charge. We believe our work advances the understanding of the effects of potential on the catalytic process in real electrochemical reactions and offers practical guidance for designing catalysts.